2003
DOI: 10.1021/jp0269322
|View full text |Cite
|
Sign up to set email alerts
|

Fast Spectroscopy of Laser-Initiated Nanoenergetic Materials

Abstract: Nanoenergetic materials consisting of aluminum nanoparticle (50−200 nm) aggregates termed ALEX plus nitrocellulose (NC) oxidizer are studied by ultrafast spectroscopy following 100 ps laser flash-heating. Thermal conduction calculations are used to estimate the initial ALEX temperature as a function of laser fluence, and to show that initiation and ignition occurs as a result of the reaction between nearly uniformly heated ALEX particles and cold NC. The onset of light emission and Al oxidation occurs near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 42 publications
1
124
0
1
Order By: Relevance
“…20 In contrast, the initial flash-heating process under low-laser-fluence ($0.3 J/cm 2 ) conditions used here is expected to produce significantly less initial heating of the absorbing aluminum nanoparticle, with temperatures ranging between the melting point (933 K) and the boiling point (2740 K) of aluminum. 3,25 The presumed mechanism for reaction of these heated aluminum nanoparticles then follows a sequence involving the breakdown of the surrounding passivation layer, the initiation of a reaction sequence between the heated aluminum and the surrounding solid-oxidant substrate material, and subsequent sustained solid-phase exothermic reactions that produce heat and light and eject aluminum nanoparticles into the surrounding environment to react with oxidants present in the gas-phase mixture. 3 At longer time delays, this explosive ejection of material from the sample surface is observed-as was the case for all experimental samples studied here-as an expanding dark plume emanating from the sample surface.…”
Section: A Temporally Resolved Shadowgraphy Of Shock Propagationmentioning
confidence: 99%
See 3 more Smart Citations
“…20 In contrast, the initial flash-heating process under low-laser-fluence ($0.3 J/cm 2 ) conditions used here is expected to produce significantly less initial heating of the absorbing aluminum nanoparticle, with temperatures ranging between the melting point (933 K) and the boiling point (2740 K) of aluminum. 3,25 The presumed mechanism for reaction of these heated aluminum nanoparticles then follows a sequence involving the breakdown of the surrounding passivation layer, the initiation of a reaction sequence between the heated aluminum and the surrounding solid-oxidant substrate material, and subsequent sustained solid-phase exothermic reactions that produce heat and light and eject aluminum nanoparticles into the surrounding environment to react with oxidants present in the gas-phase mixture. 3 At longer time delays, this explosive ejection of material from the sample surface is observed-as was the case for all experimental samples studied here-as an expanding dark plume emanating from the sample surface.…”
Section: A Temporally Resolved Shadowgraphy Of Shock Propagationmentioning
confidence: 99%
“…3,25 The presumed mechanism for reaction of these heated aluminum nanoparticles then follows a sequence involving the breakdown of the surrounding passivation layer, the initiation of a reaction sequence between the heated aluminum and the surrounding solid-oxidant substrate material, and subsequent sustained solid-phase exothermic reactions that produce heat and light and eject aluminum nanoparticles into the surrounding environment to react with oxidants present in the gas-phase mixture. 3 At longer time delays, this explosive ejection of material from the sample surface is observed-as was the case for all experimental samples studied here-as an expanding dark plume emanating from the sample surface. Mie-scattering measurements, as depicted in Fig.…”
Section: A Temporally Resolved Shadowgraphy Of Shock Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that two-component explosives consisting of metal particle fuels and oxidizers can produce more than twice as much energy as high performance molecular explosives alone (94). In recent years it has been suggested that nanometer-scale metal particles would provide faster energy release and better control over material properties, but the development of nanoenergetic materials has been hampered by the lack of fundamental knowledge of the chemical dynamics involved.…”
Section: Nanoparticle Productionmentioning
confidence: 99%